A Comprehensive Review on the Role of Lactate in Malignancy - Anvari, Kazem; Qorbani, Jafar; Javadinia, Seyed Alireza (Reports of Radiotherapy and Oncology, 2023)
Context: During a literature search, we found data indicating how lactate affects cancer patients. Evidence Acquisition: This review discusses metabolism in tumors, the lactate production pathway, and its effects on the host body. Result: Research has described high lactate concentration as an undesirable clinical condition, and lactic acidosis contributes to the death of patients or some metastatic cancers. Conclusions: Lactate can lead to angiogenesis, metastasis in the tumor, and resistance to radiation therapy and chemotherapy, especially immunosuppression. It may be possible to reduce the mortality of this disease by affecting treatment worldwide.